Comparative Evaluation of the Fluoride Content in Plant-based and Animal-based Milk: An In Vitro Study - Amitha HA; Shri Kavya A; Umaima Saleem Nadaf; Sandhya Prabha M; Nidhi J Shetty (Journal of South Asian Association of Pediatric Dentistry)
Increased fluoride ion concentrations at the dental plaque reduce the rate of demineralization, but when ingested in large amounts, it can cause enamel fluorosis. Milk has been utilized as a nutritional supplement and is already a significant component of children’s meals. Recently, plant-based milk, including oat milk, almond milk, and soy milk, has entered Indian café menus. Plant-based milk is popular among vegan populations and those with lactose intolerance. Since dental fluorosis arises from the overconsumption of fluoride during the creation of enamel, it is important to take into account all factors that contribute to the overall intake of fluoride when assessing the likelihood of developing dental fluorosis. Objective: To assess the concentration of fluoride present in animal-based milk (cow milk, buffalo milk, goat milk) and plant-based milk (oat milk, almond milk, and soy milk). Materials and methods: Three milks from the animal group and three milks from the plant group were tested. The fluoride content of these samples was analyzed using the calorimetric method (SPADNS spectrophotometer). Fluoride concentrations were compared among different groups. Results: Among plant-based milk, oat milk, almond milk, and soy milk contained 0, 1.16, and 0 mg/L of fluoride, respectively. Among animal-based milk, buffalo milk, goat milk, and cow milk contained 0.99, 0.57, and 1.39 mg/L fluoride, respectively. Conclusion: Of the examined commercially available milk (except oat and soy milk), all had fluoride content higher than normal. However, they are still unlikely to cause dental fluorosis on their own. When reconstituted with fluoridated water, and if the person consumes other fluoridated food, it may increase the risk of dental fluorosis.